Essentials of management information systems - Laudon, Kenneth C.; Laudon, Jane Price (Pearson Education, 2011)
This text contains a wealth of pedagogical features to facilitate student comprehension, which aid in reviewing and reinforcing key concepts, as well as promoting problem-solving skills.